The Influence Of Regional Financial Management Information System, The Role Of Internal Auditors And Human Resources Competence On The Quality Of Financial Statements Of Lebak Regency Government - Susana Dewi; Firmansyah Firmansyah; Herlina Herlina; Sri Intan Purnama; Anatasya Mawardiah (Nomico, 2024)
The Effect of Regional Financial Management Information Systems, the Role of Internal Auditors and Human Resource Competencies on the Quality of Lebak Regency Government Financial Statements. The purpose of this study was to examine the effect of the Regional Financial Management Information System, the Role of the Internal Auditor, and the Competence of Human Resources on the Quality of the Lebak Regency Government Financial Statements. This research uses quantitative research methods. Data obtained from primary data, namely through distributing questionnaires. This research sample was conducted at 32 OPDs in Lebak Regency. With the sample retrieval method is purposive sampling. The research respondents were PPK-SKPD (Financial Administration officer - Regional Work Unit), Treasurer and SIPKD Operator. The data processing tool used in this study used SPSS version 25 using multiple linear regression analysis techniques. The results of this study indicate that partially the Regional Financial Management Information System and the Role of the Internal Auditor have a positive and significant effect on the Quality of Financial Statements. While the Competence of Human Resources has no significant effect on the Quality of Financial Statements. And simultaneously the variables of the Regional Financial Management Information System, the Role of the Internal Auditor and Human Resource Competencies have a positive and significant effect on the Quality of Financial Statements of the Lebak Regency Government.